Maternal Hypothyroidism during Pregnancy and the Risk for Infectious Morbidity of the Offspring - Beharier, Ofer; Walfisch, Asnat; Wainstock, Tamar; Szaingurten-Solodkin, Irit; Landau, Daniela; Sheiner, Eyal (American Journal of Perinatology, 2020)
Objective Animal studies indicate a possible intrauterine immunological imprinting in pregnancies complicated by hypothyroidism. We aimed to evaluate whether exposure to maternal hypothyroidism during pregnancy increases the risk of long-term infectious morbidity of the offspring.Study Design A retrospective cohort study compared the long-term risk of hospitalization associated with infectious morbidity in children exposed and unexposed in utero to maternal hypothyroidism. Outcome measures included infectious diagnoses obtained during any hospitalization of the offspring (up to the age of 18 years).Results The study included 224,950 deliveries. Of them, 1.1% (n = 2,481) were diagnosed with maternal hypothyroidism. Children exposed to maternal hypothyroidism had a significantly higher rate of hospitalizations related to infectious morbidity (13.2 vs. 11.2% for control; odds ratio: 1.2; 95% confidence interval: 1.08–1.36; p = 0.002). Specifically, incidences of ear, nose, and throat; respiratory; and ophthalmic infections were significantly higher among the exposed group. The Kaplan–Meier curve indicated that children exposed to maternal hypothyroidism had higher cumulative rates of long-term infectious morbidity. In the Cox proportional hazards model, maternal hypothyroidism remained independently associated with an increased risk of infectious morbidity in the offspring while adjusting for confounders.Conclusion Maternal hypothyroidism during pregnancy is associated with significant pediatric infectious morbidity of the offspring.
Keywords: hypothyroidism; pregnancy; long-term infectious morbidity; retrospective cohort study